Tinjauan Literatur Pengaruh pH dan Suhu Terhadap Korosi Baja dan Anti-Fouling Kapal - Eka Cahya Muliawati; Nely Handayani; Chatarina Rista Widya Diana; Wahyu Santoso; Alimin; Amirullah; Muchlis Dermawan (JURNAL TECNOSCIENZA, 2026)
Indonesia’s maritime sector relies heavily on ships with steel-hulled structures that are susceptible to corrosion due to interaction with seawater. This corrosion rate is significantly accelerated by microenvironmental factors such as temperature fluctuations and acidity levels (pH). This qualitative study employs a literature review method to analyze secondary data from 15 reputable scientific journals published between 2021 and 2026. The results of the study show that acidic conditions (pH < 7) and rising seawater temperatures have been proven to simultaneously accelerate the corrosion rate of steel ship hull materials. As a primary protective solution, antifouling paint technology functions effectively as a dual physical barrier to break direct contact between the metal and the electrolyte while preventing the attachment of marine microorganisms. Based on a comparative matrix, spray-applied polyurethane demonstrated the most optimal protective efficiency on steel, with the lowest average corrosion rate of 2.5402 × 10?? mmpy. In addition, the use of natural materials such as sweet orange peels and kepok banana peels has great potential as environmentally friendly coating alternatives, with average corrosion rates ranging from 0.010 to 0.045 mmpy. Although the application of these coatings faces challenges such as high costs and weather-related factors, optimizing these protective coatings is crucial for improving ship operational efficiency.